Recommendation in Government Hospital Buildings in Context of Means of Escape based on Other Countries Cases - Sadek Bacha, Muhammad Amin; Suleiman, Mohd Zailan (Journal of Social Transformation and Regional Development, 2022)
The guidelines on hospital safety been developed with a target to increase the safety of a hospital structurally and functionally and decrease the risks to human’s life. The current government hospitals are mostly been built before these guidelines been developed. There are many factors that put hospitals and health facilities at high risk which includes buildings, their location, design specification and patient. For this paper, researcher’s aim is to focus on the current design specification on other countries cases and compare it with the selected government hospitals. In this paper, literature study been done thoroughly on the hospitals and cases which is caused by a poor design. Hospital may differ in area of a small hospital with a less beds and no emergency facilities or city hospital with emergency facilities including extra care, diagnostics service and hundreds of beds. Therefore, designers need to understand how each hospital operates. The latest case in our country in March 2018 is the one that occurred at Hospital Kuala Lumpur. The accident occurred at the forensic department which is caused by short circuit at its store. The fire spread very quick and destroy a portion of the forensic department. The latest incident which occurs in Hospital Sultanah Aminah (HSA) on 28th June 2020. The fire involves the oxygen panel, call bell, vacuum and switch at the bed number five. There is one more case which occurred on 26 October 2016 at Hospital Sultanah Aminah (HSA).